Research Progress on the detection methods of porcine reproductive and respiratory syndrome virus - Pan, Jinghua; Zeng, Mengyi; Zhao, Mengmeng; Huang, Liangzong (Frontiers in Microbiology, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) causes clinical syndromes typified as reproductive disorders in sows and respiratory diseases in piglets. PRRSV remains one of the most prevalent pathogens affecting the pig industry, because of its complex infection profile and highly heterogeneous genetic and recombination characteristics. Therefore, a rapid and effective PRRSV detection method is important for the prevention and control of PRRS. With extensive in-depth research on PRRSV detection methods, many detection methods have been improved and promoted. Laboratory methods include techniques based on virus isolation (VI), enzyme-linked immunosorbent assays (ELISA), indirect immunofluorescence assays (IFA), immunoperoxidase monolayer assays (IPMA), polymerase chain reaction (PCR), quantitative real-time PCR (qPCR), digital PCR (dPCR), loop-mediated isothermal amplification (LAMP), recombinase polymerase amplification (RPA), clustered regularly interspaced short palindromic repeats (CRISPR), metagenomic next-generation sequencing (mNGS), and other methods. This study reviews the latest research on improving the main PRRSV detection methods and discusses their advantages and disadvantages.